The I-mode confinement regime at ASDEX Upgrade: global properties and characterization of strongly intermittent density fluctuations. (18th October 2016) - Happel, T; Manz, P; Ryter, F; Bernert, M; Dunne, M; Hennequin, P; Hetzenecker, A; Stroth, U; Conway, G D; Guimarais, L; Honoré, C; Viezzer, E
Abstract: Properties of the I-mode confinement regime on the ASDEX Upgrade tokamak are summarized. A weak dependence of the power threshold for the L-I transition on the toroidal magnetic field strength is found. During improved confinement, the edge radial electric field well deepens. Stability calculations show that the I-mode pedestal is peeling-ballooning stable. Turbulence investigations reveal strongly intermittent density fluctuations linked to the weakly coherent mode in the confined plasma, which become stronger as the confinement quality increases. Across all investigated structure sizes ( k ⊥ ≈ 5 –12 cm −1, with k ⊥ the perpendicular wavenumber of turbulent density fluctuations), the intermittent turbulence bursts are observed. Comparison with bolometry data shows that they move poloidally toward the X-point and finally end up in the divertor. This might be indicative that they play a role in inhibiting the density profile growth, such that no pedestal is formed in the edge density profile.